THE RELATIONSHIP BETWEEN GADGET USE AND NUTRITIONAL STATUS AMONG STUDENTS AT STIKES GUNUNG MARIA TOMOHON - Priscila Evangelin Asa; Risca Manoppo (PT. Jurnal Center Indonesia Publisher, 2025)
Objective: This study aims to determine the relationship between gadget use and nutritional status in students at STIKES Gunung Maria Tomohon. Method: This study used a cross-sectional study design, conducted in December 2024 at STIKES Gunung Maria Tomohon. The number of samples was 84 respondents. Data analysis used the Spearman Rank test. Results: There is no relationship between Gadget Use and Nutritional Status, (correlation coefficient is 0.078 and Sig. 2-tailed = 0.481 <0.05). Conclusion: There is no relationship between gadget use and nutritional status at STIKES Gunung Maria Tomohon and it is recommended that the campus can improve Nutrition and Health Education in nutrition education for students. The campus can hold seminars, workshops, or classes that educate students about the importance of a healthy diet, balanced eating habits, and how to choose nutritious foods.